Bridge-inspired lattice materials with superior strength, toughness, and fatigue resistance - Heng Zhang; Junhua Ke; Jingjing Diao; Jiaqian Zheng; Naru Zhao; Yudi Kuang; Yingjun Wang (Journal of Materials Research and Technology)
A 3D-printed lattice material (LM) is a typical mechanical metamaterial with high strength, low weight, and considerable potential for application in bone implants, aircraft, and energy storage. Nevertheless, its application is limited owing to the difficulty of balancing high specific strength and toughness or fatigue resistance, which makes designing metamaterials challenging. Inspired by the excellent mechanical performance and service life of Zhaozhou Bridge, an ancient Chinese bridge, a titanium-based LM mimicking the bowstring-like rod-arch (BA) bridge structure is developed and 3D-printed. It demonstrates a compressive strength of 117 MPa at 75% porosity, two and six times higher than that of 3D-printed materials with sheet gyroid and diamond lattice structures. Moreover, it exhibits superior toughness (1271 MJ/m3) and fatigue resistance, enduring over two million cycles of cyclic compression fatigue testing. Finite element analysis and fracture characterization reveal that the excellent mechanical properties of the proposed LMs can be attributed to the BA structure's unique stress-dispersion and dual-level energy-dissipation mechanisms. Proof-of-concept demonstration results indicate that our designed BA-LMs have a great potential application in bone defect repair.